Efektivitas Penggunaan Bahan Ajar Buku Panduan Kebencanaan Di Klaten Pada Bencana Banjir Dengan Menerapkan Strategi True Or FalseDi Sma Negeri 1 Karanganom - Husein, Naza Farauk; , Dr. Tjipto Subadi, M.Si (2016)
The background of this study was the high rate of catastrophic floods that need to increase the capacity of the community to reduce the risk of disaster victims, which then started high school level students. This study aims to determine the effectiveness of the use of True Or False strategies on teaching materials sourced from the Handbook of Disaster in Klaten. This research method is experimental. The population in this study were students of SMA Negeri 1 Karanganom who participated in extracurricular school Disaster Preparedness consists of 58 students. Learning the experimental class using the strategy of True Or False. While in the control group using conventional methods or lectures. The data show that the results amounted to 52.96 pretest control class and experimental class 59.03. After learning on grade control using conventional methods or lectures posttest results obtained amounted to 67.41 and the experimental class using the strategy amounted to 84.84 True Or False. Judging from the results of both classes posttest differences are striking value. Improved learning outcomes of 25.85% indicates the effectiveness of the experimental class. As the results of hypothesis testing at posttest values that show the real difference, which is 0.00 or less than 0.05.